Irony in Roald Dahl’s The Umbrella Man Using Booth’s Theory - Salsabila, Shafwa; Nirmalawati, Widya; Wahyuningsih, Titik; Nurhayati, Sulasih (Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the use of irony in Roald Dahl’s short story The Umbrella Man using Wayne C. Booth’s theory of irony. The study aims to examine how stable and unstable irony function as narrative strategies to construct meaning and moral criticism in the story. Employing a qualitative descriptive method and close reading, the analysis focuses on narrative events, character behavior, and dialogue that reveal ironic contrasts between appearance and reality. The findings indicate that the story predominantly employs stable irony to guide readers toward a clear moral judgment, particularly through the umbrella man’s deceptive politeness and apparent helplessness. Although the narrative presents moments of moral ambiguity, these elements do not destabilize meaning but instead reinforce the satirical critique of misplaced trust and social vulnerability. The study concludes that irony in The Umbrella Man operates as a rhetorical device that shapes reader interpretation and delivers social criticism within a seemingly simple narrative.